Relationship between speech production and perception in children with Speech Sound Disorders - Berti, Larissa Cristina [UNESP]; Guilherme, Jhulya [UNESP]; Esperandino, Cassio [UNESP]; Oliveira, Aline Mara de (Ubiquity Press Ltd, 2020)
This study investigated the relationship between speech production and perception in children with Speech Sound Disorders (SSD). We hypothesized that there might be a positive correlation and the difference between speech and perceptual data for children with SSD; and that the positive correlation between speech production and speech perception errors might depend on the phonological class involved. Thirty-three children with SSD were evaluated during a speech production task and a phonological contrast identification test. The Percentage of Correct Consonant-Revised (PCC-R) and the Percentage of Correct Identification (PCI) were calculated for each child. The results of the paired t-test showed a higher perception performance mean (PCI = 87.41%) when compared to the production performance mean (PCC-R = 74.97%). The overall results of Pearson's correlation test was also statistically significant, showing a moderate, positive correlation (r = 0.49) between production and perception performances in children with SSD. The results of the correlation analyses between speech production and speech perception errors by class show that only in the fricative class, the correlation was statistically moderately significant (r = 0.52). Stops and sonorants showed no correlation. The results confirmed the relationship between speech production and speech perception, but speech perception does not mirror speech production. The positive correlation between speech production and speech perception errors depends on the phonological class.
Keywords: speech perception; speech production; speech sound disorder